Correction: Effects of ACE rs4311C>T, rs4343A>G, rs4344A>G and rs4362C>T Polymorphisms on Angiotensin-Converting Enzyme Activity among Thai Subjects - Chaikan, Ammara; Malisorn, Nipapan (Journal of Basic and Applied Pharmacology, 2020)
Correction to: Thai J Pharmacol 2019;41(2):31-42 (https://li01.tci-thaijo.org/index.php/TJP/article/view/223668)